2019
DOI: 10.1136/bmjopen-2019-029785
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of obstetric referral letters/notes from subdistrict to district level in three rural districts in Greater Accra region of Ghana: an implementation research using mixed methods

Abstract: ObjectiveTo assess the completeness of obstetric referral letters/notes at the district level of healthcare.DesignAn implementation research within three districts in Greater Accra region using mixed methods. During baseline and intervention phases, referral processes for all obstetric referrals from lower level facilities seen at the district hospitals were documented including indications for referrals, availability and completeness of referral notes/forms. An assessment of before and after intervention avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Eighteen studies (25.3%) used qualitative approaches to gain an in-depth understanding of participants’ experiences with the intervention and perceived learning. Four studies (5.6%) measured outcomes with recorded reviews in pre–post designs or RCTs [ 20 , 28 , 43 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies (25.3%) used qualitative approaches to gain an in-depth understanding of participants’ experiences with the intervention and perceived learning. Four studies (5.6%) measured outcomes with recorded reviews in pre–post designs or RCTs [ 20 , 28 , 43 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…These issues with referral documentation have been reported in other studies [ 28 30 ]. Similarly, earlier studies from Ghana have found gaps, including a lack of essential information such as the diagnosis, findings of obstetric examinations, and details concerning the care provided to manage the women’s conditions [ 8 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gaps in referral documentation indicate the need for concerted efforts by the Ghanaian central government and partner organisations to ensure that providers abide by the referral recommendations and guidelines issued by the Ministry of Health [ 9 ]. Regular professional development training, supportive supervision and feedback are required for health providers at lower healthcare levels to model the accurate completion of referral forms [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Countries where included studies were conducted comprised Ghana [22,23], Kenya [24], Mozambique [25], Nigeria [26], Rwanda [27,28], Sierra Leone [29], Tanzania [30], Uganda [31][32][33][34] and Zambia [35,36] (Figure 3). Of the 14 studies identified (Table 1), 8 were quantitative [25][26][27][28][29][32][33][34][35], including 2 RCTs [25,32], and 6 were quasiexperimental studies [22,26,28,29,[33][34][35](Table 2). Five were qualitative [22][23][24]30,31,36], with 1 mixed methods study [22] (Table 3).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%